Review of the Normativity and Historicity of Green Banking Implementation at Indonesian Sharia Banks - Lailatun Nur Suyuthi; Achmad Fageh (al-Afkar, Journal For Islamic Studies, 2024)
This research discusses the implementation of green banking at Bank Syariah Indonesia (BSI) using a normativity and historicity approach. Green banking is a banking concept that cares about the environment and sustainable profits. BSI has implemented innovative programs to support environmental sustainability and national development. The implementation of green banking is based on the normative foundations of the Koran and Islamic economic principles. This research uses library methods and approaches to normativity and historicity to analyze the implementation of green banking in BSI. Green banking is supported by Al-Maqashid al-Syariah which aims to promote community welfare by preserving the environment. The BSI has established a policy to prohibit the provision of profit support to customers whose businesses adversely affect the environment. This is in contrast to green banking which requires banks to run their business in an environmentally friendly manner and consider environmental elements when carrying out operations. BSI implements various innovative programs to support green banking practices such as paperless banking, mitigating global warming risks, and building environmentally friendly office buildings. Sustainable Financial BSI has implemented the initiation of waste management and reduction through the installation of Reverse Vending Machines (RVM) to collect plastic bottle waste for recycling. This program has succeeded in collecting large amounts of plastic bottle waste, thereby contributing to a significant reduction in carbon emissions and land conservation. This reflects growing awareness of environmental sustainability and the importance of the green economy.